Altered plasma apolipoprotein modifications in patients with pancreatic cancer: protein characterization and multi-institutional validation - Honda, Kazufumi; Felix, Klaus M.; Büchler, Markus W. (PLOS ONE, 2012)
Background: Among the more common human malignancies, invasive ductal carcinoma of the pancreas has the worst prognosis. The poor outcome seems to be attributable to difficulty in early detection. Methods: We compared the plasma protein profiles of 112 pancreatic cancer patients with those of 103 sex- and age-matched healthy controls (Cohort 1) using a newly developed matrix-assisted laser desorption/ionization (oMALDI) QqTOF (quadrupole time-of-flight) mass spectrometry (MS) system. Results: We found that hemi-truncated apolipoprotein AII dimer (ApoAII-2; 17252 m/z), unglycosylated apolipoprotein CIII (ApoCIII-0; 8766 m/z), and their summed value were significantly decreased in the pancreatic cancer patients [P = 1.36×10−21, P = 4.35×10−14, and P = 1.83×10−24 (Mann-Whitney U-test); area-under-curve values of 0.877, 0.798, and 0.903, respectively]. The significance was further validated in a total of 1099 plasma/serum samples, consisting of 2 retrospective cohorts [Cohort 2 (n = 103) and Cohort 3 (n = 163)] and a prospective cohort [Cohort 4 (n = 833)] collected from 8 medical institutions in Japan and Germany. Conclusions: We have constructed a robust quantitative MS profiling system and used it to validate alterations of modified apolipoproteins in multiple cohorts of patients with pancreatic cancer.